DEVELOPING ENGLISH SPEAKING WORKHEETS OF DESCRIPTIVE TEXT BASED ON SCIENTIFIC APPROAACH FOR STUDENTS OF MARKETING PROGRAM AT SMK NEGERI 1 MEDAN - Suci Ayu Lestari; Rahmad Husein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
DEVELOPING ENGLISH SPEAKING WORKHEETS OF DESCRIPTIVE TEXTBASED ON SCIENTIFIC APPROAACH FOR STUDENTS OF MARKETINGPROGRAM AT SMK NEGERI 1 MEDAN*Suci Ayu Lestari**Dr. Rahmad Husein, M.EdABSTRACTLestari, Suci Ayu. Registration Number: 2163321043. Developing English SpeakingWorksheets of Descriptive Text Based on Scientific Approach for Students ofMarketing Program at SMK Negeri 1 Medan. English Educational Program,Medan State University, 2021.The aim of this study was to develop English speaking worksheet of descriptive textbased on scientific approach for students of marketing program. This study wasconducted by using Research and Development (R&D) design through six stages;gathering information and data, analyzing data, designing materials, validating byexperts, revising, and final product. The subject of the study was grade X students ofSMK Negeri 1 Medan. The data were gathered by interviewing the English teacher,observing handbook, syllabus and the teaching and learning process and distributingquestionnaires to 33 respondents to get the students’ needs. The results of gathering thedata prove that the student needs English speaking worksheet which can motivate andencourage the students to speak actively in English. The result of the product was amarketing speaking worksheet based on six stages in scientific approach. The score ofvalidation from the validator was 95,3% and it was categorized as very good or relevant.Keywords:Worksheet, Speaking, Scientific Approach, English for Specific Purposes,Research and Development (R&D)